Renal macrophage infiltration is associated with a poor outcome in IgA nephropathy (Clinics, 2012)
OBJECTIVES: The objectives of our study were as follows: 1) to analyze the prognostic value of macrophage infiltration in primary IgA nephropathy (IgAN) and 2) to study the relationship between macrophages and other factors associated with the development of renal fibrosis, including mast cells, TGF-β1, α-SMA and NF-kB. METHODS: We analyzed 62 patients who had been diagnosed with IgAN between 1987 and 2003. Immunohistochemical staining was performed with monoclonal antibodies against CD68 and mast cell tryptase and polyclonal antibodies against TGF-β1, α-SMA and NF-kB p65. We also used Southwestern histochemistry for the in situ detection of activated NF-kB. RESULTS: The infiltration of macrophages into the tubulointerstitial compartment correlated with unfavorable clinical and histological parameters, and a worse clinical course of IgAN was significantly associated with the number of tubulointerstitial macrophages. Kaplan-Meier curves demonstrated that increased macrophage infiltration was associated with decreased renal survival. Moreover, the presence of macrophages was associated with mast cells, tubulointerstitial α-SMA expression and NF-kB activation (IH and Southwestern histochemistry). In the multivariate analysis, the two parameters that correlated with macrophage infiltration, proteinuria and tubulointerstitial injury, were independently associated with an unfavorable clinical course. CONCLUSION: An increased number of macrophages in the tubulointerstitial area may serve as a predictive factor for poor prognosis in patients with IgAN, and these cells were also associated with the expression of pro-fibrotic factors.